PENGEMBANGAN CORPORATE UNIVERSITY DALAM MANAJEMEN TALENTA (STUDI KASUS KEMENTERIAN PERDAGANGAN) - Srie Agustina (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2021)
According to Ministry of Administrative Reform and Bureaucratic Reform (Permenpan-RB) Number 03 of 2020 concerning State Civil Administration (SCA) Talent Management, SCA management must be supported by infrastructure through talent development programs, one of which is SCA Corporate University (CorpU). By observing the condition of learning models that are still fragmented and have not integrated a comprehensive learning model, the establishment of a CorpU at the Ministry of Trade is increasingly essential. The urgency of the formation of a CorpU is not only based on talent development which is currently not fully in line with the organization's strategic planning, but the competency improvement needs to focus more on achieving organizational performance targets. Therefore, this study aims to: (1) analyze the development of the CorpU in the Ministry of Trade ; (2) analyze the factors that become potential obstacles to the development of the CorpU; and (3) formulating the form of development through appropriate learning strategies to overcome the problems. The method used in this research is descriptive analysis and Importance and Performance Analysis (IPA). The results of the study conclude that the Ministry of Trade has implemented talent management and for that, it is necessary to implement CorpU to support talent development as one of the stages of talent management. In terms of organizational readiness, the Ministry of Trade is ready to implement CorpU. However, the Ministry of Trade needs to strengthen the Learning Strategy element, which is supported by improving the Governance and System Alignment elements. Strengthening the elements of Learning Strategy is carried out with classical learning methods (formal learning) and primarily prioritizing non- classical learning methods (informal learning). Learning innovation is needed to support the development of CorpU in the Ministry of Trade which will have a positive impact on the implementation of talent management by programming a thematic development program (TDP) and individual development program (IDP) as a Learning Journey program for the individual concerned.